(untitled) (Eurasian Journal of Engineering and Technology, 2026)
Zeolite is an aluminosilicate mineral with a three-dimensional framework structure with interconnected cavities and channels, which makes its surface area very large and effective as an adsorbent. There are currently natural and artificial types of zeolites. The high adsorption efficiency of zeolite is used as an adsorbent in all areas of the chemical industry. This scientific work obtained an alternative version of zeolite by synthesizing H-permutite based on natural raw materials. To study the characteristics of the structure of the molecular compounds of the studied samples, the Nicolet iS50 (Thermo Fisher Scientific, USA) IR-Fourier spectrometer was used. Measurements were made in the 4000-400 cm-1 spectral range, with spectral resolution not exceeding 0.1 cm. The test specimen was pressed against the mounting surface with a flat-tip probe. near, mid, and far IR attenuated total internal reflection (ATR) I S50 Analytical indicators were determined using a hole and a diamond crystal for measurement